Ozone treatment improved the extractability, bioaccessibility, and hypoglycemic potential of fresh-cut pitaya polyphenols - Li, Chen; Hu, Yishuang; Fang, Jinmiao; Du, Qiannuo; Ding, Han (Frontiers in Nutrition, 2025)
Fresh-cut fruits suffer from quality deterioration and low bioaccessibility of bound polyphenols, which limit their health benefits. This study used ozone treatment (10 μL/L for 60 min) to enhance the functional properties of fresh-cut pitaya. This treatment significantly (p < 0.05) disrupted the cell wall microstructure, increasing the extractability of free and bound phenols by 16.7 and 4.9%, respectively. This structural modification enhanced polyphenol bioaccessibility by 8% after in vitro digestion. Furthermore, the ozone-treated samples exhibited stronger inhibition of α-amylase and α-glucosidase, and in silico analyses suggested that the released polyphenols (e.g., naringin and ferulic acid) could modulate glucose metabolism via the PI3K-AKT pathway. The main advantage of this study is the direct linkage of ozone-induced microstructural changes to improved physiological functionality, positioning mild ozone treatment as a highly promising non-thermal technology that can produce health-enhanced fresh-cut fruits for the functional food market.